2019
DOI: 10.3390/en12132539
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Examination of Naturally-Aged Foam-VIP Composites

Abstract: This article describes an aging study of a foam-vacuum insulation panel (VIP) composite insulation board installed on a test wall in a natural exposure test facility through a 30-month period. Silica-based VIPs with a polymeric barrier film were used in this study. The study results showed the effectiveness of a VIP-based insulation to reduce the heat gains and losses through a wall compared to regular rigid foam insulation of the same thickness. However, the long-term performance monitoring indicated a gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…For the other materials, data were not available from the manufacturer; thus, the conductivity reported in a previous study [31] was used. In previous studies [45][46][47][48], the conductivity of a material changed with temperature and moisture content, affecting the U-value of the wall; however, this was not considered in this study. Many previous studies also utilized the conventional surface resistance values given in ISO 6946 [1] to calculate the theoretical U-value of walls.…”
Section: Test Wallmentioning
confidence: 95%
See 1 more Smart Citation
“…For the other materials, data were not available from the manufacturer; thus, the conductivity reported in a previous study [31] was used. In previous studies [45][46][47][48], the conductivity of a material changed with temperature and moisture content, affecting the U-value of the wall; however, this was not considered in this study. Many previous studies also utilized the conventional surface resistance values given in ISO 6946 [1] to calculate the theoretical U-value of walls.…”
Section: Test Wallmentioning
confidence: 95%
“…In addition to the aforementioned factors, the discrepancies between theoretical and measured values are also influenced by the nature of the wall, method of analysis, quality of construction, age of the material, and inaccurate thermophysical properties of the material. Recently, several studies have shown that the application of surface resistances that differ from onsite measurements [40][41][42][43][44] and changes in the conductivity of materials due to temperature and moisture [45][46][47][48] can be the main causes of discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, materials and technologies improving the thermal resistance of building exterior envelopes. These include advanced vacuum and electrochromic glazing [1,2], or new generation thermal insulation materials: VIP or nanotechnology based aerogel [3,4]. A considerable potential is demonstrated by the technologies based on the application of building management systems or the so-called intelligent systems that enable the building envelope characteristics to be adapted to changing weather conditions.…”
Section: Introductionmentioning
confidence: 99%